The Role of the Sarak Opat Institution in Resolving Domestic Violence Cases: A Case Study in Kampung Kung, Pegasing District, Central Aceh Regency - Firaz Mahrizka; Mahdalena Nasrun; Yusnaidi Kamaruzzaman (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
The Sarak Opat Institution functions as a central pillar of social, customary, and religious governance within the Gayo community. It operates through the collaboration of Reje, Imem, Petue, and Rakyat Genap Mufakat, including in the resolution of domestic violence (DV) cases. The existence of Sarak Opat is formally recognized in Qanun of Bener Meriah Regency Number 4 of 2015 and Qanun of Aceh Province Number 10 of 2002. In addition, the state has enacted Law Number 23 of 2004 on the Elimination of Domestic Violence, which categorizes domestic violence as a criminal offense and emphasizes legal protection for victims. However, in practice, domestic violence cases continue to occur in Kampung Kung, Pegasing District, Central Aceh Regency. Therefore, this study formulates research questions concerning: (1) the role and mechanisms employed by the Sarak Opat institution in resolving domestic violence cases; (2) the settlement of domestic violence cases under Law Number 23 of 2004; and (3) a comparison between these two legal systems. This research employs a qualitative approach with an empirical-juridical research design. Data analysis is conducted by comparing the mechanisms, authorities, and outcomes of domestic violence case resolution within both legal frameworks. The findings reveal that Sarak Opat prioritizes deliberation and reconciliation to maintain family harmony and social order, yet it has limited juridical authority in handling severe domestic violence cases. Conversely, positive law provides legal certainty and victim protection but tends to overlook the social and cultural dimensions of the community. This study concludes that resolving domestic violence cases requires synergy between customary law and positive law to achieve justice, victim protection, and social harmony.